Pengaruh Motivasi, Insentif Finansial, dan Lingkungan Kerja terhadap Kinerja Karyawan PT Daya Anugrah Mandiri Cabang Tabanan - Utama, I Ketut Pradnya; Suartina, I Wayan; Oktarini, Luh Nik (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
Employee performance will be able to remember if there is high motivation in employees in addition to that by providing fair and appropriate financial incentives and a good work environment, it can grow high employee performance. The purpose of this study is to determine the influence of motivation, financial incentives, and work environment on the performance of employees at PT. Daya Anugrah Mandiri Tabanan Branch. The number of samples in this study was 50 respondents with a saturated sample method. The data analysis technique used in this study is a research instrument test which is then continued with multiple linear regression analysis, determination coefficient test, T test and F test. The results of this study are 1) Motivation partially has a positive and significant effect on employee performance by calculating = 2,620 > ttabel value = 2,012, then H1 is accepted. 2) Financial incentives partially have a positive and significant effect on employee performance by calculating = 4,180 > ttabel value = 2,012, then H2 is accepted. 3) The work environment partially has a positive and significant effect on employee performance by calculating = 4,148 > ttabel value = 2,012, then H3 is accepted. 4) Motivation, financial incentives, and work environment simultaneously have a positive and significant effect on employee performance at PT. Daya Anugrah Mandiri Tabanan Branch. This is evidenced by the Ftabel value of 2.81 > the calculated F-126.666, so H4 is accepted. The advice given to PT. Daya Anugrah Mandiri Tabanan Branch in order to provide work motivation by working together or a team, providing holiday allowances and keeping the work environment comfortable to grow high employee performance.